A levels, readiness, and impact evaluation model for GS1 adoption in healthcare (2011)
The use of GS1 data standards is envisioned to improve the efficiency of healthcare supply chain, as it did for retail. Care providers willing to adopt such a strategy in some or all of their operations often need to invest in process changes and technological installations or upgrades; however, they struggle to project returns on those investments and hence, find uncertain ROI a barrier to adoption. We present a hierarchical comprehensive model that helps potential adopters of various parts of the standards (what we term levels) evaluate their readiness requirements and quantify the impacts of their potential decisions in terms of non-monetary performance measures, such as productivity. The model design is showcased through practical examples.